Clarifying the status of Caribbean Pinguicula (Lentibulariaceae) type specimens - Domínguez, Yoannis (Phytotaxa, 2024)
After the most recent taxonomic treatment of the genus Pinguicula in the Caribbean, several names have been found to need typification or correction of the cited type specimens. Analyses of original material and literature related to each name led to the designation of five lectotypes, one epitype and the correction of one previous inadvertent typification. Additionally, corrections to the citation of type specimens were made when necessary, including notes for each treated name. The nomenclatural status of each name for the Caribbean taxa of Pinguicula is provided.